1970
DOI: 10.1002/jso.2930020205
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic renal adenocarcinoma to the ureteral stump in a hemophiliac

Abstract: A case of a delayed distal ureteral metastasis from a cortical renal adenocarcinoma in a hemophiliac is presented as an unusual but significant problem. The need for total ureterectomy with nephreetomy is discussed. The various metastatic pathways for this tumor are presented. It would seem that the proposed avenues are, a t present, only theoretical, and it might be reasonable to assume that any one or several of them may be the pathway in an individual case. Regardless of the mode of spread, we must be cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Unless found as part of a larger report, the literature review of solid tumours excluded specific references to any type of lymphoma or Kaposi sarcoma (KS), benign solid tumours or hepatocellular carcinoma (HCC). After these neoplasms were excluded, 159 cases of malignant solid tumours in persons with haemophilia were identified with an age range of 1.9–78 years [8,15,16,18,23,27–77]. A summary of the data can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Unless found as part of a larger report, the literature review of solid tumours excluded specific references to any type of lymphoma or Kaposi sarcoma (KS), benign solid tumours or hepatocellular carcinoma (HCC). After these neoplasms were excluded, 159 cases of malignant solid tumours in persons with haemophilia were identified with an age range of 1.9–78 years [8,15,16,18,23,27–77]. A summary of the data can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It is questionable whether direct extension may be called metastasis or not, but Roller et al [23] reported a case of direct extension into the ureteral wall with no invasion into ureteral mucosa. Lymphatic spread is also imagined, but is suspicious because of the lack of con tinuity of lymphatic drainage of the kidney, ureter, and bladder [5,14], It is difficult to decide by which mechanism the métastasés in our case occurred, although the tumor protruded into the renal pel vis.…”
mentioning
confidence: 99%